A Study of Superficial Mycosis in South Gujarat Region - Parul Patel; Summaiya Mulla; Disha Patel; Gaurishankar Shrimali (Medsci Publications, 2010)
Aim: To know the seroprevalence of clinical pattern of dermatophytosis and non - dermatophytic fungi (superficial mycosis) with most common fungal pathogen in the South Gujarat region of the India. Methods: A clinical and mycological study of superficial mycosis was conducted on 198 cases (127 male and 71 female). Direct microscopy by KOH mount and culture was undertaken to isolate the fungal pathogen in each case. Results: 123 out of 198 cases (62.12%) were positive by direct microscopy in which 58 (29.29%) were positive by culture. The commonest age group involved was 21 - 30 years. Tinea corporis was the most common clinical presentation and Trichopyton rubrum was the most common fungal pathogen isolated. Non dermatophytic fungus like pityriasis versicolor and yeast like candida species were isolated in 17(22.67%) cased and 8 (10.67%) cases respectively. Conclusion: It was concluded that along with dermatophytes, nondermatophytic fungi are also emerging as important causes of superficial mycosis